The Establishment Of The Jadid Schools In Turkestan And The Process Of Education And Upbringing (The Journal of Interdisciplinary Human Studies, 2026)
This article analyses information on the establishment of the Jadid (new- method) schools in the region of Turkestan by the enlighteners of the period from the mid-nineteenth to the early twentieth century, together with the system of education, the stages of schooling, and the methods and directions of instruction. Through the activity of such figures as Mahmudkho’ja Behbudiy, Munavvar Qori, Is’hoqxon Ibrat, Saidahmad Siddiqiy, Abduqodir Shakuriy, Abdulla Avloniy, and Hamza Hakimzoda Niyoziy, it shows how the new-method school transformed literacy training, the publishing of textbooks, and the cultural life of the region.
Keywords: Turkestan; school; usul-i jadid (new method); primary grades; secondary school; higher school; new-method school; education system; madrasa; curricula